O envolvimento de idosos em atividades prazerosas: a adaptação transcultural de um instrumento - Ferreira, Heloísa Gonçalves (2011)
The sense of pleasure that arises from engagement in activities is of fundamental importance for the wellbeing of the elderly. Studies indicate that involvement in pleasant activities acts as a mediator variable in the prevention and treatment of mental disorders, in addition to predicting physical and psychological wellbeing. According to the literature reviewed to develop this study, research on this topic in Brazil is just beginning, and there is not yet an instrument, validated for use in Brazil, to evaluate the involvement of elderly people in pleasant activities. An American instrument was located in the international literature (The California Older Person s Pleasant Events Schedule - COPPES), which evaluates the frequency with which elderly people are engaged in pleasant activities and the degree of pleasure they associate with each activity. Based on its strong psychometric qualities, the inclusion of a measure to determine how each respondent felt about each activity, the ease with which the scale can be understood, and given that the items appeared to be relevant for the Brazilian culture, this instrument was selected to submit to the first steps of a cultural adaptation process, for use in Brazil. The primary objective of this study was to conduct a transcultural adaptation study (semantic equivalence, conceptual equivalence, cultural equivalence, idiomatic equivalence, operational equivalence and measurement equivalence) to prepare this instrument for use in Brazil. The main results indicate that: a) the semantic equivalence of the translated versus the original version is satisfactory; b) the items are relevant to the Brazilian cultural context and evaluate the dimensions identified by the original instrument; c) the indicator of internal consistency for the frequency and pleasantness subscales varied between very good and excellent, providing strong evidence for the internal validity of this scale; d) the frequency subscale scores were significantly correlated with the depression scores, indicating good external validity for the adapted version of this instrument. Hopefully, the new version of this instrument will contribute to research, planning, and the evaluation of preventive intervention strategies focused on promoting the wellbeing of the elderly, in Brazil.